Subfatin, asprosin, alamandine and maresin-1 in cerebral ischemia, intracranial and subarachnoid hemorrhages - Albayrak, S.; Aydin, M. A.; Ugur, K.; Hanbeyoglu, O.; Aydin, S.; Erol, E.; Aydin, S. (Verduci Publisher, 2023)
- OBJECTIVE: Cerebrovascular diseases (CVDs) remain an important public health issue due to the increasing number of deaths worldwide. Changes in the synthesis and release of peptides in CVDs may play an im-portant role in elucidating the physiopathology
Keywords: Maresin-1; Subfatin; Asprosin; Alamandine; Cere-bral ischemia; Hemorrhagy